Quality improvement teams, super-users, and nurse champions: a recipe for meaningful use?. (23rd April 2016) - Shea, Christopher M; Reiter, Kristin L; Weaver, Mark A; Albritton, Jordan
Abstract : Objective This study assessed whether having an electronic health record (EHR) super-user, nurse champion for meaningful use (MU), and quality improvement (QI) team leading MU implementation is positively associated with MU Stage 1 demonstration. Methods Data on MU demonstration of 596 providers in 37 ambulatory care clinics came from the clinical data warehouse and administrative systems of UNC Health Care. We surveyed the 37 clinics about champions, super-users, and QI teams. We used generalized estimating equation methods with an independence working correlation matrix to account for clustering within clinics and to weight contributions from each clinic according to clinic size. Results Having a QI team lead MU implementation was significantly associated with MU demonstration (odds ratio, OR = 3.57, 95% CI, 1.83-6.96, P < .001, Table 2 ). Having neither a nurse champion nor an EHR super-user was significant. Conclusion Our findings support the alignment of MU with QI efforts by having the QI team lead MU implementation.